SAT0289 Sonographic Alterations during The Course of Sjögren's Syndrome – A Five-Year Follow Up. (15th July 2016) - Hofauer, B.; Bas, M.; Mansour, N.; Loeffelbein, D.; Knopf, A.
Abstract : Background: Sonography in the evaluation of salivary gland alterations in suspected Sjögren's Syndrome (SS) and its benefit with regard to the diagnosis is part of continuing investigation. With most studies concentrating on the contribution to the diagnosis, few reports exist on longitudinal changes in the sonomorphology of salivary glands in SS. An improvement of salivary gland echostructure six months after rituximab infusion [1] and a decline of salivary gland stiffness evaluated with shear wave elastography after a two months period of a liposomal local therapy could be observed [2]. Despite intense research, many questions in ultrasound of salivary glands remain unanswered. Amongst other things it is unclear why not all patients with SS manifest sonographic abnormalities, when during the course of SS sonographic changes occur or if theses sonographic observations proceed the clinical symptomatic. Objectives: Which variation of sonographic salivary gland alterations can be observed during the five-year follow up of patients with primary Sjögren's Syndrome (pSS)? Methods: Patients with pSS diagnosed according to the AECG classification criteria were included in this study. The EULAR SS Patient Reported Index (ESSPRI) was applied for the evaluation of patient's symptoms and the EULAR SS Disease Activity Index (ESSDAI) for systemic features. During 2011 and 2016 the sonographic evaluation of salivary gland alterations in patients with primary Sjögren's Syndrome were evaluated. The echostructure of the parotid (PG) and submandibular glands (SMG) was graded on a scale of 0 to 4 (grade 0=normal, homogeneous gland; grade 1=mild parenchymal inhomogeneity (PIH), hypoechoic areas <2mm; grade 2=evident PIH, hypoechoic areas of 2–6mm; grade 3=gross PIH, hypoechoic areas >6mm; grade 4=adipose degeneration of the gland and parenchymal atrophy). Results: Fifty patients diagnosed with pSS were included (45 female, age: 56y). In 2011 the mean ESSPRI score was 8.3 (SD=4.6) and the mean ESSDAI score was 5.6 (SD=7.5). The sonographic evaluation of the PG resulted in a mean score of 1.6 (SD=0.6) and in the SMG of 1.7 (SD=1.0). The sonographic score did not correlate with the time since onset of symptoms. Clinical examination and ultrasonographic evaluation was repeated after five years in 2016, revealing a mean ESSPRI score of 6.1 (SD=3.2, p=0.002) and a mean ESSDAI score of 4.6 (SD=7.0, p<0.001). The mean sonographic score of the PG was 1.4 (SD=0.7, p<0.001) and of the SMG was 1.9 (SD=1.0, p=0.034). There was a decline in the sonographic score of the PG of 0.27 (SD=0.5) and increase of the SMG of 0.1 (SD=1.1) on average. The mean time interval between onset of first symptoms and first sonographic examination in 2011 was 57.3 months (SD=60.8). Conclusions: The five-year sonographic follow up of salivary gland alterations in patients with pSS revealed only minor alterations, even in patient with short illness duration. The relation to systemic or local therapeutic interventions is part of on-going analysis. References: Jousse-Joulin S, Devauchelle-Pensec V, Cornec D et.al. Brief Report: Ultrasonographic Assessment of Salivary Gland Response to Rituximab in Primary Sjögren's Syndrome. Arthritis Rheumatol. 2015 Jun;67(6):1623–8 Hofauer B, Bas M, Heiser C et.al. FRI0388 Monitoring Local Therapy in Sjögren's Syndrome with Virtual Touch Tissue Quantification Sonography. Ann Rheum Dis 74(Suppl 2):567.2 Disclosure of Interest: None declared